Augmenting the Grammar of Science—The Community Science Exchange. Issue 2 (30th June 2022) - Noone, Kevin J.; Schensul, Jean J.; Buchanan, Paula R.
Abstract: The expanding field of community science offers the possibility to augment the way science is done, making closer, two‐way connections between researchers, communities, and community members. It enriches and improves science through broadening the scope of problem and hypothesis formulation to include practitioners who will use the results of scientific investigation. It enriches the communities involved through access to and participation in scientific investigations aimed at their own challenges. In this article, we describe a new facility—the Community Science Exchange —that offers venues for both researchers and community practitioners to publish and share their work to the benefit of both science and communities. Plain Language Summary: We are in a new epoch in which society needs to deal with "wicked" problems—such as sustainably producing healthy, nutritious, affordable, and attractive food for everyone on the planet while enhancing ecosystem resilience, dealing with climate change, transforming our energy and transport sectors, and ensuring just and equitable access to resources. Dealing with these sorts of problems challenge the research community to become more connected to society, and to more holistically involve communities and practitioners in the process of science. In this article, we describe a new facility that offers venues for publishing, promoting and rewarding science done with, not for, communities. Key Points: Community science—new knowledge co‐produced by researchers and community members—has the potential to enrich science through broadening our research perspectives, help communities respond to their pressing challenges, increase equitable access to science, and increase the understanding of and support for science in society The grammar of science is important; while we currently focus mainly on nouns and verbs (i.e., our results and methods), we need to augment our grammatical treasure chest with prepositions (science "with" society, not "for" or "on"), prefixes (i.e., trans‐disciplinary science is different from inter‐ and multi‐disciplinary science), and adverbs describing how we work (e.g., collaboratively)